PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA KARYAWAN (STUDI KASUS PADA BANK BNI 46 KANTOR CABANG PERINTIS KEMERDEKAAN BANDUNG) - RISKY CAHYO PRASETYO (JURNAL EKOBIS DEWANTARA, 2018)
The purpose this experiment is to describe (1) the effect of leadership style on job satisfaction at the Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung (2) the effect of work motivation on job satisfaction at the Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (3) the effect of job satisfaction on the performance of employees at Bank BNI 46 Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (4) the effect of leadership style on employee performance at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (5) The effect of work motivation on employee performance in Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung. The results showed that (1) Style of leadership significant positive effect on job satisfaction at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (2) work motivation significant positive effect on job satisfaction at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (3) job satisfaction significant positive effect on the performance of employees at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (4) leadership style is not significant positive effect on the performance of employees at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung, (5) work motivation is not significant positive effect on the performance of employees at Bank BNI 46 kantor cabang Perintis Kemerdekaan Bandung.